HUBUNGAN POLA ASUH MAKAN DENGAN STATUS GIZI ANAK BALITA DI POSYANDU PALA INDAH V PARAK LAWEH PULAU AIE KECAMATAN LUBUK BEGALUNG KOTA PADANG - WULANDARI, SUCI; Yulastri, Asmar; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The objective of study was toanalyzethe relationbetweenchild feeding practiceandchildnutritional status inPosyanduPala Indah VParak Laweh. Researchiscorrelationalbypopulationisall children areincluded inthe workingareaPosyanduPala Indah V Parak Laweh. Sampleswereselected bysamplingsaturatedby 49people. The results of the research show that feeding practice as much as 8 % of children included is excellent category, 10% of children included good category, 27% of children included quite well, 22% of children included unfavorable category and 33 % of children included category of not good. The results of the study showed that the nutritional status of children are 2 children (4%) included excellent category, 4 children (8% ) included goodcategory, 6 children (1%) included good category, 13 children (27% ) included unfavorable category and 24 children (49%) included category of no good. There isa positiverelationshipbetweenfeeding practicewith thenutritional status of childreninPosyanduPala Indah V Parak Lawehwith correlation coefficient0.722. Keywords: feeding practice, nutritional status